Arthralgias, fatigue, paresthesias and visceral pain: can joint hypermobility solve the puzzle? A case report. Issue 1 (December 2016) - Folci, Marco; Capsoni, Franco
Abstract Background Joint hypermobility syndrome describes a disorder in which musculoskeletal pain occurs in a generalized joint hypermobility substrate. The clinical picture comprises variable manifestations which involve mainly but not exclusively the musculoskeletal system, and evolve over the person's lifetime. Case presentation Describing the case of a 20-year-old female with generalized arthro- myalgias, persistent fatigue and troublesome visceral pain, we illustrate how a frequently ignored clinical sign such as joint hypermobility can be the keystone to clarify different simultaneous symptoms. All of the patient's physical complaints had been investigated separately during her previous medical examinations, and several tests repeatedly gave negative results. The patient received different diagnoses that describe only part of her problems, such as irritable bowel syndrome for visceral pain, fibromyalgia for arthralgias or depression for fatigue. These approaches gave rise to pharmacological or physical treatments which did not improve her quality of life in any way and in some instances worsened the situation. Pronounced joint hypermobility which led the patient to flex her joints excessively, causing subluxations in several districts, was the only sign overlooked. Conclusion Exploring the patient's articular features in her clinical context led us to diagnose joint hypermobility syndrome, a complex and often ignored condition. The case highlights the utility of a multidisciplinary approach and coordinated interventions to define and manage this clinical entity.